2008
DOI: 10.1227/01.neu.0000335078.62599.14
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of Safety and Efficacy of Nicardipine and Nitroprusside Drip for Control of Hypertension in the Neurosurgical Intensive Care Unit

Abstract: When used for control of hypertension in patients with subarachnoid or intracerebral hemorrhage, NC and SNP were both safe and effective, but patients on an NC drip required fewer dose adjustments and fewer additional medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…This medication, however, was deemed inadequate for BP control and had to be changed to SN in only one infusion (2%). Our results mirror those by Roitberg et al, who found BP to be outside the pre-specified goal in 38% of the nicardipine infusion time [18] and Liu-Deryke et al, who found that 40% of nicardipine-treated patients with ICH failed to meet the BP goal within 24 h [19]. There are several potential contributors to this suboptimal BP response.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This medication, however, was deemed inadequate for BP control and had to be changed to SN in only one infusion (2%). Our results mirror those by Roitberg et al, who found BP to be outside the pre-specified goal in 38% of the nicardipine infusion time [18] and Liu-Deryke et al, who found that 40% of nicardipine-treated patients with ICH failed to meet the BP goal within 24 h [19]. There are several potential contributors to this suboptimal BP response.…”
Section: Discussionsupporting
confidence: 86%
“…No rebleeding occurred in these patients, which may be due to a combination of BP control and early treatment of the culprit lesion. Vasospasm occurred in 50% of patients, identical to that found in the study, which compared nicardipine to SN [18]. The three deaths that occurred in our patient population were temporally unrelated to nicardipine.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…ICP decreased during the infusion and serial computerized tomographic (CT) scans did not demonstrate any evidence of rebleeding or exacerbation of edema. A recent clinical trial comparing nicardipine and nitroprusside in 163 neurosurgical intensive care patients noted no clinically serious elevated ICP in either group [18]. However, this study reported only serious adverse events secondary to raised ICP and prospective recording of ICP was not included.…”
Section: Discussionmentioning
confidence: 95%
“…A variety of titratable medications are available. Nicardipine may give smoother blood pressure control than labetalol 135 and sodium nitroprusside, 136 although data showing different clinical outcomes are lacking. Although lowering cerebral perfusion pressure may lead to cerebral ischemia, a cohort study of neurologically critically ill patients did not find an association between use of nicardipine and reduced brain oxygen tension.…”
Section: Medical Measures To Prevent Rebleeding After Asahmentioning
confidence: 99%